For here or takeaway - Bong, Brian Peng Long (Nanyang Technological University, 2020)
Everything related to food is subjective, from how one perceives what tastes good to how it should be prepared. Anyone who claims to love food is bound to have their opinions and preferences about what makes what their experiences genuine. This is especially so in Singapore’s local food scene which has seen traditions transform into some of the most modern takes on our own cuisine. How, then, could one determine what is the true and correct way to go about our favourite dishes? What makes or breaks the authenticity of the food that we as a country identify to be locally ours? For Here or Takeaway is a photographic project that attempts to question the meaning of authenticity within our local food culture, one that found its own persona through the migrants of its early days, and to consider its place and relevance as popular Singaporean dishes westernize under the guise of evolution in an attempt to suit the modern-day Singaporean and foreign palate. The project invites individuals to reflect upon what truly matters about their local food as they are presented in different, literal forms; based on their personal upbringing, familiarity and understanding of what is presented.